Massive Development of E-Testing Questions - Ristov, Sashko; Gushev, Marjan; Armenski, Goce (My University, 2015)
This paper presents several techniques and strategies for massive e-testing questions generation. These techniques can be used to develop a large set of questions and assessment content. A pilot project is presented in achieved speedup of questing development for single- and multiple-choice questions, as well as questions with two options (true/false).
Keywords: eAssessment, eTesting system, question database, knowledge evaluation